Conflict and moral change: LGBTQ plus rights education, religion and renegotiation - Hämäläinen, Nora Fiona Karolina (Wiley-Blackwell, 2021)
In this paper, I address a complex of challenges around religiously grounded ethical ideas in education, the public sphere and public institutions, focussing on the question of LGBTQ+ rights education and an exemplary conflict over this topic in Birmingham, England, in 2019. I argue that it is important, both theoretically and practically, to approach the issue, not just as a conflict between religious and liberal/secular world views, but also as a product of relatively rapid historical change in moral understandings, which has not been equally distributed in the populations that are affected by it. I revisit (1) the genealogy of current liberal conceptions on marriage, sexuality and partnership; (2) Paul Rabinow's pluralist notion of 'the contemporary' and (3) the clashing vulnerabilities of groups involved in contemporary conflicts over religion and sexual identity, to offer historically and socially sensitive tools for both theoretical and practical renegotiation.
Keywords: clashing vulnerabilities; LGBTQ plus rights education; liberalism; moral change; Paul Rabinow; religion